Anovaginal Colonization by Group B Streptococcus and Streptococcus anginosus among Pregnant Women in Brazil and Its Association with Clinical Features - Natalia Silva Costa; Laura Maria Andrade Oliveira; Andre Rio-Tinto; Isabella Bittencourt Ferreira Pinto; Ana Elisa Almeida Santos Oliveira; Julia de Deus Santana; Laiane Ferreira Santos; Rayssa Santos Nogueira Costa; Penelope Saldanha Marinho; Sergio Eduardo Longo Fracalanzza; Lucia Martins Teixeira; Tatiana Castro Abreu Pinto (MDPI AG, 2024)
Streptococcus agalactiae (Group B Streptococcus; GBS) is a leading cause of neonatal invasive disease worldwide. GBS can colonize the human gastrointestinal and genitourinary tracts, and the anovaginal colonization of pregnant women is the main source for neonatal infection. Streptococcus anginosus, in turn, can colonize the human upper respiratory, gastrointestinal, and genitourinary tracts but has rarely been observed causing disease. However, in the last years, S. anginosus has been increasingly associated with human infections, mainly in the bloodstream and gastrointestinal and genitourinary tracts. Although anovaginal screening for GBS is common during pregnancy, data regarding the anovaginal colonization of pregnant women by S. anginosus are still scarce. Here, we show that during the assessment of anovaginal GBS colonization rates among pregnant women living in Rio de Janeiro, Brazil, S. anginosus was also commonly detected, and S. anginosus isolates presented a similar colony morphology and color pattern to GBS in chromogenic media. GBS was detected in 48 (12%) while S. anginosus was detected in 17 (4.3%) of the 399 anovaginal samples analyzed. The use of antibiotics during pregnancy and history of urinary tract infections and sexually transmitted infections were associated with the presence of S. anginosus. In turn, previous preterm birth was associated with the presence of GBS (p < 0.05). The correlation of GBS and S. anginosus with relevant clinical features of pregnant women in Rio de Janeiro, Brazil, highlights the need for the further investigation of these important bacteria in relation to this special population.